Small hepatocellular carcinoma treated with percutaneous RF ablation: MR imaging follow-up - Sironi,, S; Del Maschio,, A; De Cobelli,, F; Ferrero,, CG; Meloni,, F; Livraghi, , T (1999)
OBJECTIVE, The purpose of our study was to determine the usefulness of MR imaging in the follow-up evaluation of small hepatocellular carcinoma lesions treated with RF ablation.